The Development of Domino Ceria Learning Media to Enhance Number Concept Understanding in Children Aged 4–6 Years - Heni Puspita Sari; Nita Priyanti; Debie Susanti (Kirana Publisher (KNPub), 2026)
Most children still have difficulty connecting number symbols with objects, ordering numbers, and performing simple arithmetic operations. This condition is exacerbated by limited availability of engaging learning media appropriate to early childhood development. Therefore, learning media development is needed. Domino Ceria (DORIA) is a set of domino cards with an attractive visual design used to improve understanding of number concepts in children aged 4–6 years. The research method used in this study is Research and Development (R&D) with the ADDIE model. The research subjects were Group B children of Trisula Perwari Kindergarten aged 4–6 years. The research instruments included needs analysis, expert validation, and effectiveness testing. The results showed that the Domino Ceria media met feasibility standards with an average percentage of 97.00% based on expert validation and proved effective in improving children's understanding of number concepts.